2020
DOI: 10.1101/2020.08.25.266635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting transcriptional responses to cold stress across plant species

Abstract: Although genome sequence assemblies are available for a growing number of plant species, gene expression responses to stimuli have been catalogued for only a subset of these species. Many genes show altered transcription patterns in response to abiotic stresses. However, orthologous genes in related species often exhibit different responses to a given stress. Accordingly, data on the regulation of gene expression in one species are not reliable predictors of orthologous gene responses in a related species. Her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Previous applications of machine learning across species yielded similar results (Lee, Karchin, and Beer 2011; Chen, Fish, and Capra 2018; Kelley, n.d.; Mejía-Guerra and Buckler 2019). For example, Meng et al trained machine learning models to identify cold-responsive genes across a few different grass species (Meng et al 2021). Consistent with our results, models performed best when trained and tested in the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous applications of machine learning across species yielded similar results (Lee, Karchin, and Beer 2011; Chen, Fish, and Capra 2018; Kelley, n.d.; Mejía-Guerra and Buckler 2019). For example, Meng et al trained machine learning models to identify cold-responsive genes across a few different grass species (Meng et al 2021). Consistent with our results, models performed best when trained and tested in the same species.…”
Section: Discussionmentioning
confidence: 99%
“…In a study led by Meng et al (2021), supervised classification models were employed to identify genes responding transcriptionally to cold stress. Surprisingly, models trained solely with features derived from genome assemblies displayed modest reductions in performance compared to those incorporating a wider range of data.…”
Section: Ai-assisted Transcriptomicsmentioning
confidence: 99%
“…The switchgrass cold response RNA-seq data were from a published study of a time course (0.5, 1, 3, 6, 16, and 24 hrs) under cold treatment (6°C) with paired control samples (29°C/ 23°C in a 12-h/12-h day/night cycle) (Meng et al, 2021). Switchgrass transcriptomes under three other stress conditions were from three published studies [Dehydration ( (Zhang et al, 2018)), salt ), and drought ( (Zuo et al, 2018)].…”
Section: Transcriptome Data Collection Preprocessing and Gene-set Enr...mentioning
confidence: 99%
“…In switchgrass, coexpression analysis has been used to establish the potential transcriptional regulatory networks in heat, drought, and biotic stress conditions (Pingault et al, 2020;Hayford et al, 2022;Zhou et al, 2022). Recently, a comprehensive, transcriptomic study on several panicoid grasses, including switchgrass, revealed that machine learning approaches can be implemented to predict cold stress responses of genes within and between species based on nucleotide frequencies in promoter regions of genes, among other features (Meng et al, 2021). Beyond nucleotide frequencies, a similar approach using longer nucleotide sequences (i.e., k-mers) can identify putative cisregulatory elements that are regulatory switches of gene expression under cold stress in switchgrass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation